Hypermasculine language in the expression of Good Kids Movie - Nadiyatusy Syarifah Nur Baiti; Toyyibah Toyyibah (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
Teenager life is often challenging, and faces many problems. The movie portrays the struggle of a group of friends to be accepted by doing some activities called machismo. It shows the crucial moment of their life to focus on masculine things. This study aims to analyze the practices of  Hypermasculinity through the expression in the movie. This research is qualitative. The researcher collected the data by observing the movie. The finding showed that the characters in the movie adopt all three features of Hypermasculinity practices. Thus acts are drinking alcohol, partying, drugs, violence, and sexual behavior